Utilization of Service Oriented Architecture to Customize Accounting Business Process in Open ERP System for Smart SME’s - Muhardi Saputra; Sanny Putra Hendarsyah; Wahjoe Witjaksono (School of Industrial and System Engineering, Telkom University, 2020)
Small and medium enterprises or commonly referred to as SMEs in Indonesia are business activities that are in great demand after the economic crisis which resulted in the termination of employment (PHK) experienced by most companies. The role of SMEs in the Indonesian economy has now been recognized by the wider community. However, many SMEs in Indonesia are still running their business processes separately, especially in the accounting system, so that the business processes are running poorly, financial transactions that are still recorded and reported manually and separately, sales/purchase account items that are still recorded manually, and there's no system that supports the accounting process for SMEs.The output from this research is an Open Source ERP-based Smart SME system design in the accounting module by embedding the